Adsorption of Polyvinylpyrrolidone over the Silica Surface: As Affected by Pretreatment of Adsorbent and Molar Mass of Polymer Adsorbate - Laila M. Al-Harbi; Samia A. Kosa; Musa K. Baloch; Qaisar A. Bhatti; El-Sayed El-Badawey H. El-Mossalamy (International Journal of Polymer Science)
The adsorption of polyvinylpyrrolidone over the surface of silica has been investigated. The impact of molar mass of the polymer, pH, and pretreatment temperature of silica particles have been evaluated by means of FTIR spectroscopy and electrophoretic measurements. The silica particles used have narrow particle size distribution. The zeta potential of the aqueous silica suspension was decreased with the increase in pH. The amount of polymer adsorbed was increased with the increase in pretreatment temperature, time, concentration, pH, zeta potential, and molar mass of the polymer. The addition of polymer to the system increased the zeta potential due to adsorption of polymer on the surface of the particles. However, the impact increased with the increase in molecular mass of the polymer. The IR spectra obtained before and after adsorption of polymer concluded that, mostly, hydrogen bonding is responsible for the adsorption phenomena; however, hydrophobic interactions also play a significant role. The mechanism has been investigated and established through FTIR spectroscopy.